The Involvement of Secondary Neuronal Damage in the Development of Neuropsychiatric Disorders Following Brain Insults - Chen, Yun; Garcia, Gregory; Huang, Wei; Constantini, Shlomi (Frontiers in Neurology, 2014)
Neuropsychiatric disorders are one of the leading causes of disability worldwide and affect the health of billions of people. Previous publications have demonstrated that neuropsychiatric disorders can cause histomorphological damage in particular regions of the brain. By using a clinical symptom-comparing approach, 55 neuropsychiatric signs or symptoms related usually to 14 types of acute and chronic brain insults were identified and categorized in the present study. Forty percent of the 55 neuropsychiatric signs and symptoms have been found to be commonly shared by the 14 brain insults. A meta-analysis supports existence of the same neuropsychiatric signs or symptoms in all brain insults. The results suggest that neuronal damage might be occurring in the same or similar regions or structures of the brain. Neuronal cell death, neural loss, and axonal degeneration in some parts of the brain (the limbic system, basal ganglia system, brainstem, cerebellum, and cerebral cortex) might be the histomorphological basis that is responsible for the neuropsychiatric symptom clusters. These morphological alterations may be the result of secondary neuronal damage (a cascade of progressive neural injury and neuronal cell death that is triggered by the initial insult). Secondary neuronal damage causes neuronal cell death and neural injury in not only the initial injured site but also remote brain regions. It may be a major contributor to subsequent neuropsychiatric disorders following brain insults.